Solid Self-Microemulsifying Drug Delivery System for Improved Oral Bioavailability of Relugolix: Preparation and Evaluation - Li ZL; Deng GX; Fang CZ; Zhao YQ; Yuan J; Chen L; Zhong HJ; Guo F (International Journal of Nanomedicine)
Zi-Lin Li,1,* Guo-Xing Deng,1,* Chuan-Zhou Fang,1,* Yue-Qi Zhao,1 Jing Yuan,2 Liang Chen,3 Hai-Jun Zhong,1 Feng Guo1 1School of Pharmacy, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China; 2College of Basic Medicine and Forensic Medicine, Henan University of Science and Technology, Luoyang, 471000, People’s Republic of China; 3Jiangxi Prozin Pharmaceutical Co., LTD, Jian, 343100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Guo; Hai-JunZhong, School of Pharmacy, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China, Tel +86 0791 86361839, Email fengguo@ncu.edu.cn; zhonghj@ncu.edu.cnPurpose: To improve the oral absorption of relugolix (RLGL), which has low oral bioavailability due to its low solubility and being a substrate of P-glycoprotein (P-gp). A solid self-microemulsifying drug delivery system of relugolix (RLGL-S-SMEDDS) was prepared and evaluated in vitro and in vivo.Methods: The composition of the solid self-microemulsifying drug delivery system (S-SMEDDS) was selected by solubility study and pseudo-ternary phase diagram, and further optimized by Design-Expert optimization design. The optimized RLGL-S-SMEDDS were evaluated in terms of particle size, zeta potential, morphology analysis, thermodynamic stability, drug release, flow properties, transporter pathways in Caco-2 cells, the influence of excipients on the intestinal transporters, transport within Caco-2 cell monolayers and transport in lymphocyte. In vivo pharmacokinetic study and toxicological study were also conducted.Results: The optimum formulation for self-microemulsifying drug delivery system (SMEDDS) consists of Ethyl Oleate (26% of the weight), Solutol HS15 (49% of the weight), Transcutol HP (25% of the weight) and loaded relugolix (4.8 mg/g). The S-SMEDDS was then formed by adsorbing 2.4 g of SMEDDS onto 1 g of hydrophilic-200 silica. In phosphate buffered saline (PBS) (pH 6.8) release medium containing 1% tween 80, the vitro release studies showed 86% cumulative drug release for RLGL-S-SMEDDS and 3.6% cumulative drug release for RLGL suspensions. In vitro cellular uptake experiments revealed that the uptake of RLGL-S-SMEDDS by Caco-2 cells was three times higher than that of free RLGL, and that S-SMEDDS can enhance the drug absorption through lymphatic absorption and inhibition of intestinal transporter. In vivo pharmacokinetic evaluation demonstrated that the oral bioavailability of RLGL-S-SMEDDS was 1.9 times higher than that of RLGL-suspensions. There was no apparent cardiac, hepatic, splenic, pulmonary or renal toxicity on the surface discovered by pathological analysis after oral administration.Conclusion: It is evident that S-SMEDDS may be a safe and effective method to improve oral absorption of drugs with low oral bioavailability. Keywords: solid self-microemulsifying drug delivery system (S-SMEDDS), relugolix, microemulsion, oral bioavailability, P-glycoprotein